ANALISIS PERBANDINGAN LIKUIDITAS, SOLVABILITAS DAN RENTABILITAS PADA KINERJA KEUANGAN BANK SWASTA YANG TERDAFTAR DI PT. BURSA EFEK INDONESIA PERIODE 2013-2015 - brahmayanti, sri; najar, azizah (Fakultas Ekonomi dan Bisnis, Universitas 17 Agustus 1945 Surabaya, 2017)
ABSTRAKA good performance of a bank is expected to regain public confidence in the bank itself or the banking system as a whole. Financial performance can be known by calculating the financial ratios so that it can know the performance and using ratio analysis, namely the ratio of liquidity, solvency, and profitability. This ratio analysis is a technical analysis to determine the relationship between certain items in the balance sheet or income statement bank individually or collectively. The purpose of this study is to compare the financial performance of four private banks listed on the Indonesia Stock Exchange. The results of the analysts show that there are differences in financial ratios, namely the ratio of liquidity, solvency, and rentability in private banks registered in PT. Indonesia Stock Exchange period 2013-2015.Â Keywords: Ratio Analysis, Financial Performance Analysis, Bank.ABSTRAKA good performance of a bank is expected to regain public confidence in the bank itself or the banking system as a whole. Financial performance can be known by calculating the financial ratios so that it can know the performance and using ratio analysis, namely the ratio of liquidity, solvency, and profitability. This ratio analysis is a technical analysis to determine the relationship between certain items in the balance sheet or income statement bank individually or collectively. The purpose of this study is to compare the financial performance of four private banks listed on the Indonesia Stock Exchange. The results of the analysts show that there are differences in financial ratios, namely the ratio of liquidity, solvency, and rentability in private banks registered in PT. Indonesia Stock Exchange period 2013-2015.Â Keywords: Ratio Analysis, Financial Performance Analysis, Bank.